Potret Tradisi Tahfiz Al-Qur’an di SDIT Kota Langsa (Analisis Kondisi dan Signifikansiya Terhadap Peningkatan Kemampuan Membaca Al-Qur’an) - Mulizar, Mulizar (Fitrah: Journal of Islamic Education, 2021)
This study aims to analyze the portrait of Al-Qur'an tahfiz activities that have a good influence on the ability to read the Qur'an in integrated Islamic schools in Langsa city. This paper is the result of a case study research using a descriptive analysis method with a qualitative approach, where the main data sources are observation and interviews, and documentation. The results of this study explain that the process of implementing memorizing the Qur'an to improve the ability to read the Qur'an carried out by SDIT Langsa students is that students are divided into two levels, namely basic (guidance) and intermediate (Tahsin). The students with basic level (guidance) get the memorization by listening (sima'i) from the teacher in class. The teacher mentally qinkan to students by repeating each verse that is read properly and correctly and followed by students several times, according to the target of memorizing verses per day, and it turns out that in general students are able to memorize the Qur'an by listening (sima'i). ). Meanwhile, students with intermediate level (tahsin) acquire memorization using the independent rote method.